DYNAMIC RESPONSE OF A FLEXIBLE SPACECRAFT STRUCTURE DUE TO ATTITUDE CONTROL GENERATED MOTION - Kevin, Alexander
In the dynamic structural analyses of spacecraft, the structures are typically considered multibody mechanical systems consisting of rigid and flexible parts. The dynamic attitude of the rigid body, i.e., a spacecraft body, induces structural deformation in the flexible parts. The flexible structure response, in return, may also affect the control system's performance and quality in regulating the spacecraft's attitude. The present work investigates a flexible spacecraft structure's dynamic characteristics and responses due to an attitude control command's action. In the present work, two flexible spacecraft models are used: (1) a flexible solar panel used as a preliminary work, and (2) a set of three flexible solar panels connected by rigid hinges and yoke. Modal analyses evaluate the models' natural frequencies and mode shapes. In addition, dynamic response analyses are done in frequency and time domains. The frequency and time response analyses evaluate the structures' responses exerted by harmonic loads to verify the modal analyses' results. Furthermore, control torque in the form of one sinusoidal wave (pulse) is applied as the excitation load. Control torque concerning the rigid body's pitch motion excites the panel's torsional modes. In contrast, vertical (heaving) and rotational flapping (rolling) motions exert the bending modes. Therefore, the flexible responses result in pointing disturbances compared to the rigid body attitude. The panels are shown to oscillate with the attitude value as the reference axis. Most cases are depicted to have pointing disturbances up to 5% of the attitude values.